2014
DOI: 10.5539/ass.v10n3p1
|View full text |Cite
|
Sign up to set email alerts
|

Attitude, Parental Encouragement and Perception of the Importance of English in English Language Learning

Abstract: This study investigated the students' perception of the importance of English language amongst a sample of 150 Upper Six students from a population of 755 students from six schools in the district of Marang, Terengganu. Also studied was whether their attitude towards learning English language is positive and whether they receive sufficient parental encouragement and support in their English language learning. It was found that the students were well aware of the importance of English language and also had a ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…( The participants' statements suggest that encouragement from immediate family positively impacts a child's motivation, a notion supported by research. Jaliyya and Idrus (2017) highlighted the significance of parental encouragement in children's English language motivation, while Nair, Setia, Mohamad, Kadir, Luqman, Vadeveloo, and Ngah (2014) linked parental support to students' English proficiency. Tahaineh and Daana (2013) found that a majority of their respondents reported high levels of external locus of control and motivation in learning English, with significant parental encouragement and recognition of the language's importance.…”
Section: • Positive Family Cloutmentioning
confidence: 99%
“…( The participants' statements suggest that encouragement from immediate family positively impacts a child's motivation, a notion supported by research. Jaliyya and Idrus (2017) highlighted the significance of parental encouragement in children's English language motivation, while Nair, Setia, Mohamad, Kadir, Luqman, Vadeveloo, and Ngah (2014) linked parental support to students' English proficiency. Tahaineh and Daana (2013) found that a majority of their respondents reported high levels of external locus of control and motivation in learning English, with significant parental encouragement and recognition of the language's importance.…”
Section: • Positive Family Cloutmentioning
confidence: 99%
“…No obstante, en la actualidad, la mayor parte de la población no domina el uso del inglés a pesar de estar incluido en el plan de estudios desde el primer curso de primaria (Sekharan et al, 2014). Esto puede deberse a que la instrucción y la evaluación a la que se somete el alumnado es pasiva y no tiene en consideración las diferencias individuales y las necesidades de aprendizaje de cada alumno y alumna en particular (Arteaga, 2011;Prato y Mendoza, 2006).…”
Section: Introductionunclassified